MODEL PEMBERDAYAAN NELAYAN MISKIN DI KOTA KENDARI PROVINSI SULAWESI TENGGARA - Rahim, Manat; Thahir, Madjiani; Ahmad, Ahmad; Baso, Jamal Nasir (JURNAL KEBANGSAAN, 2019)
This study aimed to analyze the poverty fisherman factors and empowering model. The data used in this research is primery data. The samples were taken from there districts, namely Poasia, Abeli and Kendari district whichan chosen employing proportionally sampling . The results of the research indicated that the factors fisherman poverty is economic and social factors such as capital, education level, the number of the famly member and the effective fishing daytime. Poverty alleviation model approach , shows that economic empowering 65, 5 % increased in famly income and vetura capital empowerment fisherman increased fishing activity and manged marine product with a success rate 45 % and 55 % did not success. Keywords : Fisherman poverty and empowering model